Magnetic Coupling between Metal Spins through the 7, 7, 8, 8‐Tetracyanoquinodimethane (TCNQ) Dianion. Issue 25 (7th May 2014) - Saber, Mohamed R.; Prosvirin, Andrey V.; Abrahams, Brendan F.; Elliott, Robert W.; Robson, Richard; Dunbar, Kim R.
Abstract: A family of magnetic metal–organic frameworks, (Ph3 PMe)2 [M2 (TCNQ)3 ] {M=Fe 2+, Co 2+, Ni 2+ and Zn 2+ } have been prepared and structurally characterized. The honeycomb‐like "layers" consist of M II ions doubly bridged with dinitrilomethane moieties of two 7, 7, 8, 8‐tetracyanoquinodimethane (TCNQ) dianions which are further connected through phenyl rings to form a 3D dianionic framework [M2 TCNQ3 ] 2− with Ph3 PMe + cations filling cavities that run along the c axis. Studies of the magnetic coupling through the TCNQ dianion in these structures revealed that it can promote long‐range magnetic ordering despite the long coupling pathway. Abstract : Dianionic coordination framework : A family of magnetic metal–organic frameworks, {(Ph3 PMe)2 [M2 (TCNQ)3 ]∞ (M=Fe 2+, Co 2+, Ni 2+, Zn 2+ ) has been prepared and found to consist of a 3D trigonal network with (Ph3 PMe) + cations occupying cavities that run along the c axis (see figure). The honeycomb‐like "layers" contain M II ions doubly bridged with dinitrilomethane moieties of two 7, 7, 8, 8‐tetracyanoquinodimethane (TCNQ) dianions, which are further extended through phenyl rings to form the 3D dianionic framework [M2 TCNQ3 ] 2− .